HYPOGLYCAEMIC EFFECTS OF JAVANESE GINSENG (Talinum paniculatum (Jacq.) Gaertn.) ROOT INFUSION ON ALLOXAN-INDUCED DIABETIC RATS - Ikhlas Muhammad Jenie; Rosefani Intan Indraswari (Universitas Syiah Kuala, 2021)
To examine whether Javanese ginseng root has an antihyperglycaemic effect, twenty-one male Rattus norvegicus rats were randomly divided into four groups: negative control (n= 3), positive control (n= 4), treatment (n= 7), and placebo (n= 7). Alloxan was injected intraperitoneally at a single dose of 80 mg/kg BW to rats to induce hyperglycaemia. Infusion of Javanese ginseng root or distilled water was given at a dose of 2% w/v solution with a volume of 1.8 mL/200 g BW per day for 14 days through an enteral feeding tube to either the treatment or placebo group, respectively. Blood glucose levels were measured using the colorimetric method. One-way analysis of variance (ANOVA) was used to examine differences in the mean of delta blood glucose (post intervention minus post alloxan blood glucose levels) among groups, followed by Tukey’s post hoc analysis. A P value 0.05 was considered statistically significant. There was a significant difference (P= 0.0001) in delta blood glucose among groups. Post hoc analysis revealed that delta blood glucose in the treatment group (-102.99±2.26 mg/dL) was significantly (P= 0.0001) greater than in the placebo (2.45±0.29 mg/dL), positive control (3.05±0.70 mg/dL) and negative control (1.60±0.17 mg/dL) grou p. In conclusion, Javanese ginseng root has potential as a hypoglycemic agent in alloxan-induced diabetic animal models